Qur’anic Verse Therapy for Early Childhood: A Living Qur’an Study at PAUD IT Kebon Ilmu Probolinggo - Ghozi Mubarok; Muhammad Ulul Albab (Penerbit Hellow Pustaka, 2025)
The Qur’an can serve as shifa’ (a cure, remedy, and source of solutions) for individuals experiencing sadness, adversity, or various life challenges. In this context, Qur’anic verses function as psychological therapy and as a remedy for the problems faced by individuals. The researcher identified a Living Qur’an phenomenon occurring at an early childhood education institution in Probolinggo, namely PAUD IT Kebon Ilmu. The school provides Qur’anic verse therapy to its students, who consist not only of typically developing children but also those with developmental disorders or specific conditions. This study focuses on two main points: First, how Qur’anic verse therapy is implemented for early childhood students. Second, the methods used in administering Qur’anic verse therapy to early childhood students. This research employs a qualitative field approach with a descriptive design. Data were collected through interviews, observations, and documentation, with teachers and parents of PAUD IT Kebon Ilmu serving as informants. The findings of this study are as follows: (1) The implementation of Qur’anic verse therapy for early childhood students at PAUD IT Kebon Ilmu is based on the belief that the Qur’an is the foundation of children’s character. The types of therapy practiced at the school include Qur’an recitation therapy combined with speech therapy, behavior therapy, and fine motor therapy. (2) The methods of Qur’anic verse therapy used at PAUD IT Kebon Ilmu include murottal therapy in all student activities, UMMI method Qur’an learning, special-needs (ABK) therapy—mostly conducted by the principal—and the Tabarak method implemented at noon while students wait to be picked up by their parents.